(3GdeYOI HjJ GdOGAs - (3YHO GdQMef Hf eMeO Hf eMeO, GHf NdOhf CHh RjO, hdqj GdOjf GdMVQeqj GdETHjdj,J (B808 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GYde Cf GUd GdCeQGV cdgG EfeG gh ef GdCZPjI , ceG bGd Udi Gddg Ydjg hSde ai GdMOjK GdLGeY ddWH , hgh bhdg (B:" (3GdeYOI HjJ GdOGA hGdMejI QCS GdOhGA (B" s
(3BNQgG (B:s
(3hbO jeQV GdYVh hjMOK Yfg eQV Gdbhi GdehLhOI dg gPg cdgG LeGY GdCeQGV hCUdgG ai GdZGdH ai GdCZPjI , gPG cdg eOahY Edi GdWHjH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B330 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B188s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdKGfi (B- (3U (B235 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(474(3c(B) s
Keywords: (3GdWHs